New data on distribution and biology of Blastobasis glandulella (Riley, 1871) (Lepidoptera: Blastobasidae) in Ukraine - Zinchenko, O. V.; Sokolova, I. M.; Skryknyk, Yu. Ye.; Borysenko, O. I.; Kukina, O. M. (The Kharkiv Entomological Society Gazette, 2023)
Blastobasis glandulella (Riley, 1871) is an invasive species North American origin that is known from Ukraine since 2009. The species was identified based on imago and caterpillars. The species is confirmed to occur in seven regions of Ukraine: Zakarpattia, Ivano-Frankivsk, Kyiv, Poltava, Ternopil, Khmelnytskyi, and Cherkasy. Caterpillars was found inside acorns of pedunculate oak (Quercus robur L.). The moths begin emerges at the end of May–the beginning of June, and lasts until the beginning of August. Caterpillars overwinteres inside acorns on the soil surface and in the forest litter. Pupation takes place inside acorns. The species is potential dangerous for forestry. Diagnostic features of imago, larva and pupa are given and illustrated. 10 figs, 23 refs.
Keywords: invasive species; distribution; oak; acorn